Relevansi Konsep Pendidikan Islam Pada Masa Khulafaurrasyidin Dengan Pendidikan Indonesia - Amyus, Randi Saputra; Roza, Ellya (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The aim of this research is to analyze the relevance of the concept of Islamic education during the Khulafaurrasyidin period to Indonesian education. This type of research is a library study. Data collection with documentation. Data analysis with SLR. The research results The concept of Islamic education during the Khulafaurrasyidin era has strong relevance to education in Indonesia today, especially in terms of moral and ethical values ​​that are integrated into the education curriculum. During Khulafaurrasyidin's time, education did not only focus on mastering knowledge but also on character formation based on Islamic teachings, such as honesty, justice and social responsibility. These principles are reflected in the Indonesian education system which prioritizes the development of national character and the formation of individuals with integrity and noble character. By adopting these values, Indonesian education seeks to produce a generation that is not only intellectually intelligent but also moral and contributes positively to society.